Analisis Pengaruh Bauran Pemasaran Terhadap Peningkatan Volume Penjualan Padi Kelompok Tani Kembang Mekar di Desa Tal Kecamatan Satar Mese - Santu, Lorensius; Payong, Polikarpus; Piran, Ronaldus Don; Jandu, Inosensius Harmin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to find out how the marketing mix influences the increase in rice sales volume of the Kembang Mekar Farmers Group. The marketing mix is one of the factors that can influence the increase in sales volume of a product. The marketing mix itself consists of four elements, namely product, price, promotion and distribution. In the context of the Kembang Mekar farmer group, it is important to analyze the influence of the marketing mix on increasing rice sales volume. Thus, this research aims to identify factors in the marketing mix that can increase the sales volume of rice for the Kembang Mekar farmer group. In the context of ideal conditions, the Kembang Mekar farmer group is expected to be able to increase rice sales volume significantly. The location of this research was carried out at the Kembang Mekar farmer group. Determining the location of the research was carried out deliberately. The time for conducting the research is from February to May 2024. Product and price have a significant influence on the volume of rice sales in the Kembang Mekar farmer group, while place and promotion do not have a significant influence individually.